Analisis Kebutuhan Pengembangan e-LKPD Pembelajaran Berdiferensiasi Pada Konsep Asam-Basa - Anggraeni, Maya Erliza; Abudarin, Abudarin; Sadiana, I Made; Fatah, Abdul Hadjranul; Asi, Nopriawan Berkat (Jurnal Ilmiah Kanderang Tingang, 2024)
This study aims to analyze the need for the development of differentiated learning-based e-Worksheet (e-LKPD) on the acid-base concept at SMA Negeri 2 Palangka Raya. Differentiated learning allows teachers to present materials and assessments tailored to students' varying abilities and learning styles. The research method used is qualitative descriptive, with data collection techniques including questionnaires, interviews, and observations involving teachers and students. The results show that teachers need a comprehensive, interactive, and flexible e-LKPD with adjustable content and exercises of varying difficulty levels. Students desire a visually appealing e-LKPD that is easily accessible across multiple devices and includes interactive features and instant feedback. In conclusion, the development of a differentiated learning-based e-LKPD is essential for improving the effectiveness of teaching the acid-base concept, supporting individual differences among students, and facilitating active engagement in learning.